2018
DOI: 10.3389/fpsyg.2018.00908
|View full text |Cite
|
Sign up to set email alerts
|

Believing What You're Told: Politeness and Scalar Inferences

Abstract: The experimental pragmatics literature has extensively investigated the ways in which distinct contextual factors affect the computation of scalar inferences, whose most studied example is the one that allows “Some X-ed” to mean Not all X-ed. Recent studies from Bonnefon et al. (2009, 2011) investigate the effect of politeness on the interpretation of scalar utterances. They argue that when the scalar utterance is face-threatening (“Some people hated your speech”) (i) the scalar inference is less likely to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…At first sight, these results are opposed to those of Bonnefon and his colleagues but another recent study using response times (Mazzarella et al, 2018) suggests how they could be made compatible. Replicating the methodology followed by Bonnefon and his colleagues and positing that the prevalence of one-sided readings in their studies was due to a failure to distinguish between (initial) comprehension of the SI and its (subsequent) acceptance, they divided the experimental task into two parts and elicited subjects' responses as well as reaction times to two different questions.…”
Section: 2contrasting
confidence: 75%
See 3 more Smart Citations
“…At first sight, these results are opposed to those of Bonnefon and his colleagues but another recent study using response times (Mazzarella et al, 2018) suggests how they could be made compatible. Replicating the methodology followed by Bonnefon and his colleagues and positing that the prevalence of one-sided readings in their studies was due to a failure to distinguish between (initial) comprehension of the SI and its (subsequent) acceptance, they divided the experimental task into two parts and elicited subjects' responses as well as reaction times to two different questions.…”
Section: 2contrasting
confidence: 75%
“…The fact that face-threat is best construed as a matter of situational context (section 3.1) highlights the importance of a few other situational factors, starting with participant gender. The nexus of im/politeness and gender has been primarily studied by sociolinguists (for a recent overview, see Chalupnik et al, 2017; for a recent experimental study using ERP s, see Jiang & Zhou 2015: 257-259), who found that women tend to use more indirect strategies overall, one explanation for which is that they tend to construe the same acts as more face-threatening than men do.14 The fact that samples were not balanced for gender in any of the previous experiments (women outnumbered men by as much as 4.5 to 1 in Bonnefon et al, 2009;Feeney & Bonnefon, 2012;Holtgraves, 2014;Holtgraves & Perdew, 2016; men outnumbered women in Mazzarella et al, 2018) could be yielding a somewhat biased picture in this regard. To alleviate this concern, a gender-balanced sample was used in the study reported below.…”
Section: Residual Considerationsmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Bonnefon and Villejoubert (2006) argue that the face‐saving flavour of modal expressions such as possible is crucially arrived at pragmatically, taking into account both the form's conventional content and the utterance context. Evidence for this is that the process whereby politeness is inferred also carries important consequences for other aspects of the semantic interpretation of the expression; for example, it inhibits the scalar implicatures that the use of such expressions would normally license (see Bonnefon, Feeney, & Villejoubert, 2009; Mazzarella, Trouche, Mercier, & Noveck, 2018 for further discussion). In a similar vein, Jeong (2019) suggests that the politeness effects linked to rising declaratives can be derived via the same primitive communicative principles that inform other kinds of non‐truth‐conditional inferences.…”
Section: Modeling Social Meaningsmentioning
confidence: 99%